Significantly Increased CD70 Up Regulation on TEL-AML Positive B Cell Precursor Acute Lymphoblastic Leukemia Cells Following CD40 Stimulation - Troeger, A.; Glouchkova, L.; Ackermann, B.; Escherich, G.; Hanenberg, H.; Janka, G.; Roettgers, S.; Göbel, U.; Dilloo, D. (Klinische Pädiatrie, 2014)
Background: TEL-AML the most common genetic alteration in childhood precursor B acute lymphoblastic leukemia (BCP-ALL) is associated with a favorable prognosis.Patients and method: We studied the expression of nerve growth factor/tumor necrosis factor receptor (NGFR/TNFR)/ligand family members on 108 primary BCP-ALL samples by flow cytometry and compared both their baseline expression and CD40-induced modulation on TEL-AML positive and negative leukemia samples.Results: Our findings demonstrate that TEL-AML positive patients exhibit a significantly higher percentage of CD40, CD27 and p75NTR positive blasts at diagnosis. This might well contribute to the improved relapse-free survival of these patients assessed in Kaplan Meier analysis as CD27 and p75NTR directly mediate apoptotic signals. Furthermore CD40 ligation enhances antigen presenting and T cell stimulatory capacity via significant up regulation of CD70 while adequate response to physiological maturation signals as indicated by concomitant down regulation of CD27 is retained in TEL-AML positive leukemia.Conclusion: These data provide novel insights in immunological control mechanisms preserved in this leukemia subtype and suggest that not only treatment with chemicals such as HDAC inhibitors but also retained in vivo response to CD40 ligation contributes to improved immune surveillance in these patients which may add to a superior relapse-free survival observed particularly in the presence of other risk factors.
Keywords: acute leukemia; TEL-AML rearrangements; TNF receptors; immune response